(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2024)
Feed in a poultry industry is a critical component in t he production of broilers for marketing, this factor is very important as it must contain significant percentages of nutritional compounds that provide production performance in both production and economy and must have quality for its implementation. This research was carried out to evaluate the microbiological quality of different concentrates used for broiler production, taking into account the different stages that broilers go through to achieve optimal growth; To evaluate the quality of the different concentrates, assemblies were carried out by homogenising the samples in peptonised water, and then sowing by depletion on different agars such as MacConkey, Plate Count, EMB, XLD and PDA, to analyse, evaluate and identify the different microorganisms that can alter the nutritional functionality of the concentrate in poultry production. Results were obtained such as growth of Gram-positive bacteria such as Bacillus subtilis, fungal structures such as non-septate hyphae representing the genus Mucor and identification of Salmonella and Escherichia coli strain, which was confirmed through biochemical tests. These microorganisms present a warning point for the poultry industry, as they are affecting the nutritional level of production in the poultry farms.